Effects of A Multisensory-Based Mindfulness Program on Stress and Anxiety Levels in People Living with HIV Who Use Methamphetamine - Jaknissai, Jeerawit; Suebphanphoe, Chakkraphan; Nithikathkul, Choosak (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
HIV infection is associated with methamphetamine use, particularly among men who have sex with men (MSM), and may contribute to neuropsychiatric consequences such as heightened stress and anxiety, which can adversely affect daily functioning and engagement in meaningful daily activities. Although various interventions are available to address stress and anxiety, many present practical and clinical limitations in their application. This case study investigated the effects of a multisensory-based mindfulness program on stress and anxiety in an individual with methamphetamine use and co-existing HIV infection. The program was implemented through three principal occupational therapy processes: (1) evaluation, (2) intervention, and (3) outcome assessment. Occupational history and occupational performance were evaluated using the Occupational History Interview (OHI), Suanprung Stress Test-20 (SPST-20), Generalized Anxiety Disorder Scale-7 (GAD-7), and Canadian Occupational Performance Measure (COPM), administered before and after the intervention. The findings indicated that participation in the multisensory-based mindfulness program was associated with reductions in both stress and anxiety. Specifically, stress scores decreased from 50 (high) to 33 (moderate), while anxiety scores declined from 7 (mild) to 2 (minimal). In addition, improvement was observed in the health management domain, reflected by increased occupational performance (4.5-point increase) and satisfaction (5.5-point increase). However, these results are preliminary and based on a single participant; therefore, studies with larger samples and longer-term follow-up are needed to confirm the program’s effectiveness and assess the sustainability of its outcomes.